STRATEGI PENINGKATAN PENGELOLAAN ARSIP MELALUI PENGAWASAN KEARSIPAN INTERN: Array - Lufi Herawan (Arsip Nasional Republik Indonesia, 2019)
National Archives of Indonesia as one of the government creating agencies should carry out their own records management to ensure the availability of archives in carrying out activities as performance accountability material and legal evidence. In the internal archival supervision conducted by ANRI, it turns out that the results of the internal archival monitoring results are not in accordance with the targets set. Based on these problems, records management should be improved so that they can be better. This research will determine the strategy of records management in the ANRI environment so that it can improve the management of records in its environment. This research is desk research based on primary data from internal archival monitoring results within the ANRI environment, and the determination of strategy is carried out using content analysis of audit instruments containing elements and sub-elements that must be met. After analyzing, it is obtained the strategy of creating archives according to TND and the implementation of vital archive programs in the Work Unit. Whereas the Archives Unit II is more concerned with managing inactive records, disposal, and accessing records.